TYPICAL BEHAVIOUR OF JUVENILE DELINQUENCY IN SENIOR HIGH SCHOOL STUDENT (JURNAL KESEHATAN MERCUSUAR, 2019)
This study aims to see how the typical behavior of juvenile delinquency is carried out by high school students. This research uses a qualitative approach. Taking participants in this study using purposive sampling techniques with the characteristics of participants is a teenage student in high school who lived separately from his parents since the beginning of high school with a research location in one private school. Researchers also use key person techniques, where researchers get complaints from several teachers from the school. The number of clients in this study was 1 person. Data collection techniques with semi-structured interviews, semi-participant observation and data analysis were performed using thematic analysis. This study revealed the typical symptoms/ behavior of juvenile delinquency displayed by the client. The negative behavior of these participants raises problems in the field of education and relationships with family and social environment.
Keywords: Typical Behavior, Juvenile Delinquency, high school students